Flood impact assessment in Kota Bharu, Malaysia: a statistical analysis - Mohammad Muqtada Ali Khan; Nor Ashikin Shaari; Arham Muchtar Achmad Nahar; Md. Azizul Baten; Dony Adriansyah Nazaruddin (2014)
Floods are common natural disaster occurring in most parts of the world. It is considered to be one